KINERJA PENGURUSAN PENGELOLAAN BARANG MILIK DAERAH PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN ENREKANG - Hariyanti Hamid; Abdul Rahman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The purpose of this research is: To know the Performance of Management in the Management of Regional Property at the Secretariat of the Regional House of Representatives of Enrekang Regency.The type of research that the authors select is descriptive research with quantitative approach. The research was conducted at the Secretariat of the Regional House of Representatives of Enrekang Regency. The population in this study is all the staffs in the Secretariat of the Regional People's Legislative Assembly of Enrekang Regency as many as 58 people and the samples amounted to 58 people. Data collection techniques used are: 1) Interview 2) Documentation 3) observation 4) Questionnaire. The results showed that 1). The performance of managers in the management of local property at the Secretariat of the Regional House of Representatives of Enrekang Regency can be seen in the following: Job performance, Expertise, Behavior, and Leadership on average percentage of 74.31% on good criteria. 2). Factors affecting the performance of management in the management of local property at the Secretariat of the Regional House of Representatives of Enrekang Regency can be seen in the following: Employee quality of 84.13%, Supporting facilities of 77.24%, Supra means of 40.0% , Capability of 64.82%, and Motivation of 76.89% with an average percentage of 68.616% on influential criteria.